An exploratory study conducted in Hong Kong looked at how a nursing education program and counselling service affected patients with chronic obstructive pulmonary disease’s quality of life and adherence to their medications. - HU YUE, HU YUE; DR FARIDAH MOHD SAID, DR FARIDAH MOHD SAID (International Journal of Multidisciplinary Research and Studies, 2024)
People with chronic obstructive pulmonary disease often struggle with not using their inhalers as needed. As a result, this lowers one's health and overall quality of life (QoL). A number of studies have shown that patients who strictly follow their medication schedules had fewer hospitalizations and a better quality of life. The quality of life and adherence to treatment for chronic obstructive pulmonary disease (COPD) have been shown to improve with nurse education and counselling. An effective new method to enhance medicine adherence and patient quality of life in COPD patients is a nursing education and counselling programme. This dissertation seeks to do three things: (1) study and construct a strategy for implementing an educational programme in a clinical setting; (2) establish a protocol for evidence-based practise; and (3) analyse the possibility for implementing the approach. From two different online databases, six studies meeting the criteria were selected. Studies were critically evaluated to ensure they were of sufficient quality and validity. SIGN (Scottish Intercollegiate Guidelines Network) checklists were utilised for the evaluation (SIGN). The collected data was subsequently analysed. The implementation's viability and adaptability were evaluated. The practical viability of the evidence-based recommendations was also taken into account. The next stage was to find out if clinical ideas supported by evidence were feasible for healthcare practitioners to execute. After this, we'll talk about the potential downsides and upsides of emerging technologies and tinker with the cost-benefit analysis. Additionally, the EBP procedure was developed with real-world clinical use in mind.